Frasa Bahasa Melayu Jambi di Desa Jambi Tulo Kecamatan Maro Sebo Kabupaten Muaro Jambi - Chindi Pramudya Wardani; Kamaruddin Kamaruddin; Akhyarudin Akhyarudin (Jurnal Ilmiah Dikdaya, 2023)
This study aims to describe the forms and meanings of Jambi Malay phrases in Jambi Tulo Village, Maro Sebo District, Muaro Jambi Regency. The method in this research is qualitative research with descriptive method. Data collection in the study of Jambi Malay phrases was obtained through several research techniques, namely interview techniques, listening techniques, recording techniques, and note taking techniques. The amount of data obtained in this research on Jambi Malay phrases is 31 utterances of Jambi Malay. Based on data analysis, it was found that phrases in Jambi Malay can be distinguished into (a) endocentric phrases which include coordinating endocentric phrases, appositive endocentric phrases, and attributive endocentric phrases. (b) exocentric phrases consisting of directive and non-directive exocentric phrases. The forms of phrases in Jambi Malay are based on phrase categories, namely verbal, nominal, numeral, adjective, and prepositional phrases. The meaning relationship between the elements in Jambi Malay phrases are the meanings of verb phrases, noun phrases, numeral phrases, and prepositional phrases